Accountable government through collaborative governance? - Eva Sørensen; Jacob Torfing (Administrative Sciences, 2021)
Governance researchers have repeatedly discussed how to make public governance more accountable given the relatively 'thin' accountability of representative government. Recent decades have seen the growth of new, compensatory forms of accountability. However, these measures do not seem have satisfied the demands for strengthening public sector accountability. Drawing on the concept of social accountability, this article challenges common wisdom in arguing that collaborative governance may enhance public governance accountability, although it also raises new accountability problems that must be tackled. The article develops a heuristic framework for empirical studies of accountability, which improves the impact of collaborative forms of governance.
Keywords: 350; collaborative governance; metagovernance; public accountability; representative democracy; social accountability